2021
DOI: 10.1093/mnras/stab1739
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a possible high-confidence radio quasi-periodic oscillation in the BL Lac PKS J2134–0153

Abstract: Using the Lomb–Scargle periodogram and the weighted wavelet Z-transform techniques, we have searched for quasi-periodic oscillations (QPOs) of the BL Lacertae object (BL Lac), PKS J2134–0153, in the 15-GHz radio light curve announced by the Owens Valley Radio Observatory 40-m telescope during the period from 2008 January 5 to 2019 May 18. This is the first time that the search for periodic radio signals in the BL Lac PKS J2134–0153 has used these two methods, which consistently reveal a QPO of 4.69 ± 0.14 yr (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…It not only can bury possible QPOs signal, but also may spuriously mimic few-cycle sinusoid-like periods (Krishnan et al 2021). Covino et al (2019) has showed that some periodicities reported in AGNs appears poorly justified, but Ren et al (2021) said that red noise can hardly be responsible for long-term QPOs. In the paper, the influence of red noise is eliminated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It not only can bury possible QPOs signal, but also may spuriously mimic few-cycle sinusoid-like periods (Krishnan et al 2021). Covino et al (2019) has showed that some periodicities reported in AGNs appears poorly justified, but Ren et al (2021) said that red noise can hardly be responsible for long-term QPOs. In the paper, the influence of red noise is eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…However, so small space separation in BBH model is also reported in literature, such as used BBH model to explain QPOs with periodicity of 850 days in OT 081, with estimated space separation about 0.0076 pc. Jet procession (Caproni et al 2013;Mangalam 2018;Ren et al 2021) is also a possible explanation for the QPOs shown in the long-term light curves. It assumes helical structure in a relativistic jet (Bhatta 2018;.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we also consider a supermassive black hole binary (SMBHB) system to explain the long-term periodic temporal signals. Sillanpaa et al (1988) (Ren et al 2021a). The Keplerian orbital motion of an SMBHB would trigger periodic accretion perturbations, or the gravitational torque from a companion would induce the jetprecessional and nutational motions in misaligned disk orbits and yield periodic timescales in the range of ∼1 to ∼25 yr (Katz 1997;Rieger 2004;Komossa 2006;Cavaliere et al 2017, and reference therein).…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, Li et al (2021) found about 850 days of periodic modulation in all three bands (4.8, 8, and 14.5 GHz) of the BL Lac OT 081, and a pure geometric scenario provided a plausible explanation for the detected QPO. Interestingly, a QPO of ∼4.69 yr (>5σ confidence level) was found in PKS J2134-0153, in which the 15 GHz light curve is very close to sinusoidal variation (Ren et al 2021a). Then some possible QPOs have also been studied in J1359+4011, PKS 0219-164, J1043+2408, and PKS J0805-0111 (King et al 2013;Bhatta 2017Bhatta , 2018Ren et al 2021b).…”
Section: Introductionmentioning
confidence: 93%
“…Unlike those found in gamma-ray, these X-ray QPO signals oscillate on timescales of hours or days, and no reliable QPO signals have been reported on long timescales (year-like oscillation) (Stella & Vietri 1998;Gierliński et al 2008;Lin et al 2013;Pan et al 2016;Zhang et al 2017bZhang et al , 2018. FSRQ J1359+4011, PKS J0805-0111 and BL Lac PKS 0219-164, PKS J2134-0153 are reported to have QPO signals in the radio band, most of which are on the timescale of years (King et al 2013;Bhatta 2017;Ren et al 2021aRen et al , 2021b. S5 0716+714 is a very famous BL Lac object, which has been monitored by many telescopes for a long time, and has a redshift of z = 0.31 (Donato et al 2001).…”
Section: Introductionmentioning
confidence: 88%